The Effect of Peers and Parents’ Economy on the Interest of Students in Class XII SMA Negeri 2 Semendawai Barat to Continue to Higher Education - Iskandar, Iskandar; Lian, Bukman; Putra, Muhammad Juliansyah (Journal of Social Work and Science Education, 2023)
This study aims to determine: (1) the influence of peers on interest in continuing to higher education; (2) parents’ economic influence on interest in continuing to higher education; (3) the influence of peers and the economy of parents together on the interests of class XII students of SMA Negeri 2 Semendawai Barat Continuing to Higher Education. The population in this study were class XII students at SMA Negeri 2 Semendawai Barat for the 2022/2023 academic year. The sample in this study amounted to 83 students with probability sampling technique. Data collection techniques using a questionnaire. The data analysis technique in this research is prerequisite test and hypothesis test. The results of this study are: (1) The positive and significant influence of peers on the interest of class XII students at SMA Negeri 2 Semendawai Barat to continue higher education for the 2022/2023 academic year. This is indicated by a t-score of 8.255, a regression coefficient of 0.693, and a significance value of 0.000. Based on these conclusions, it can be said that the better the peers, the greater the interest in continuing to higher education. (2) The positive and significant financial impact on parents’ interest in continuing higher education in class XII students of SMA Negeri 2 Semendawai Barat for the 2022/2023 academic year.